Grain boundary electric characterization of Zn7Sb2O12 semiconducting ceramic: A negative temperature coefficient thermistor - Nobre, MAL; Lanfredi, S. (American Institute of Physics (AIP), 2003)
The electrical properties of the grain boundary region of electroceramic sensor temperature based on inverse spinel Zn7Sb2O12 were investigated at high temperature. The zinc antimoniate was synthesized by a chemical route based on the modified Pechini method. The electric properties of Zn7Sb2O12 were investigated by impedance spectroscopy in the frequency range from 5 Hz to 13 MHz and from 250 up to 600 degreesC. The grain boundary conductivity follows the Arrhenius law, with two linear branches of different slopes. These branches exhibit activation energies with very similar values; the low-temperature (less than or equal to350 degreesC) and high-temperature (greater than or equal to400 degreesC) regions are equal to 1.15 and 1.16 eV, respectively. Dissimilar behavior is observed on the relaxation time (tau) curve as a function of temperature, where a single slope is identified. The negative temperature coefficient parameters and nature of the polarization phenomenon of the grain boundary are discussed. (C) 2003 American Institute of Physics.